Optical fiber vibration sensor for automated inspection of industrial assets - Costa, Ciro Matheus De Lima; Gonçalves, Maria Eduarda Benfica; Ramalho, Jessica Guerreiro Santos; Silva, Lucas Cruz Da; Dias, Paula Do Patrocinio; Almeida, Jamile Santos; Silva, Douglas Lima; Silva, Valeria Loureiro Da (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2023)
Vibration pattern of industrial assets is characteristic of the operating state of the structure. In environments with difficult access and explosive atmospheres, inspection of this vibration pattern can be performed using robotic manipulators. In this work, an optical fiber vibration sensor embedded in a silicone elastomer was developed and characterized. The vibration sensor is based on macrobending losses and can be interrogated by monitoring the transmitted optical power. The simple detection system combined with the small size and weight of the sensor makes it suitable for incorporation into a robotic manipulator. The test results show a good correlation between the acceleration and vibration frequency measured by the optical fiber sensor and commercial accelerometer and vibrometer. Therefore, the concept of a vibration sensor based on a fiber coil embedded in silicone is a viable alternative for measuring vibration in places where electronics may pose a risk of explosion, such as oil production platforms.